ZAKAT LEMBAGA KEUANGAN SYARIAH SEBAGAI BADAN HUKUM - Imam Mustofa (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2014)
Normatively zakat of asset that must be payed is 5 kinds, namely: cattle, agriculture, trade alms, gold and silver, and rikaz. Some contemporary scholars like Yusuf Qaradawi, Ali al-Salus, Muhyiddin al-Ashfar perform ijtihad of Islamic law related to the development of various assets must be payed a zakat. Yusuf Qaradawi, for example, based on the results of his ijtihad, considering the realities of modern economic activity, he recommended nine kinds of asset that must be payed zakat. He added 4 assets, namely: honey and animal production, minerals and marine products, investment in plant, buildings, zakat profession, stocks and bonds. Furthermore, contemporary scholars also discussed the obligation of zakat institution or legal entity. Based on the ijtihad, Islamic Financial Institutions is obligated to pay zakat because it is a subject of law and as well as a profitable business entity.